PREPARATION OF THE TEXT OF AN INTERNATIONAL TREATY (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article discusses the main stages and principles of preparing the text of an international treaty. Legal, lexical, and stylistic aspects are discussed, as well as the importance of complying with international standards and norms. Special attention is paid to the role of negotiations and consensus between the parties, as well as the process of ratification and implementation of the treaty into national legislation.